Radial head excision and Achilles allograft interposition arthroplasty for the treatment of chronic pediatric radiocapitellar pathologies: A report of four cases. (April 2021) - Factor, Shai; Rotman, Dani; Pritsch, Tamir; Allon, Raviv; Tordjman, Daniel; Atlan, Franck; Rosenblatt, Yishai
Background: Severe radiocapitellar pathologies represent a unique problem in the pediatric population, as radial head excision can lead to substantial long-term complications. We present a case series of four pediatric patients treated by a novel technique—radial head excision followed by Achilles allograft interposition arthroplasty. Methods: Four children (ages 12–15 years) are described. Their clinical and radiographic outcomes were assessed by a visual analog scale, the Mayo Elbow Performance Score, the Disabilities of the Arm, Shoulder and Hand questionnaire, grip strength, and range of motion. Results: At a mean follow-up of two years, the average flexion-extension arc of motion improved from 107° to 131°, and the rotation arc improved from 100° to 154°. The average visual analog scale, Mayo Elbow Performance Score, and Disabilities of the Arm, Shoulder and Hand scores were 2, 92.5, and 11.5, respectively. Two patients required subsequent additional procedures—manipulation under anesthesia and ulnar shortening osteotomy. Proximal migration of the radius was observed in three out of the four patients. Discussion: Combined radial head excision and Achilles allograft interposition arthroplasty represents a viable option for the treatment of chronic pediatric radiocapitellar pathologies, with good results in terms of clinical and functional outcomes as well as patient satisfaction in the short-medium term.